Deteksi Jawaban Buatan AI pada Tugas Pemrograman Berbasis Sistem Penilaian Otomatis - Ahmad Muyassar Ibrahim (Sakura Publisher, 2026)
The use of artificial intelligence (AI) by students in completing programming assignments continues to increase and has created new challenges in maintaining academic integrity. This study examines the patterns and prevalence of AI-generated answers in programming assignments submitted through a Learning Management System (LMS) equipped with automatic assessment features. The LMS used in this study was developed using the ADDIE model and integrated with an AI detection mechanism as the data collection platform. This study involved 109 students from two courses, namely Basic Web Programming and Mobile Programming, at UIN Alauddin Makassar during the Even Semester of the 2026/2027 academic year. From a total of 186 assignment submissions, the system identified 49 submissions, or 26.3%, as answers suspected to have been generated using AI. The analysis covered the distribution of flagging across courses, score comparisons before and after penalties, and the general characteristics of answers indicated as AI-generated. The results show that the level of AI use in Indonesian-language programming assignments is relatively high, with TGS-642 in the Web Programming course recording the highest flagging percentage at 41.5%. This study contributes to understanding the phenomenon of generative AI use in Indonesian programming education and offers practical recommendations for managing academic integrity.